Study on Surface Roughness, Morphology, and Wettability of Laser-Modified Powder Metallurgy-Processed Ti-Graphite Composite Intended for Dental Application - Peter Šugár; Richard Antala; Jana Šugárová; Jaroslav Kováčik; Vladimír Pata (Bioengineering, 2023)
In this study, the surface laser treatment of a new type of dental biomaterial, a Ti-graphite composite, prepared by low-temperature powder metallurgy, was investigated. Different levels of output laser power and the scanning speed of the fiber nanosecond laser with a wavelength of 1064 nm and argon as a shielding gas were used in this experiment. The surface integrity of the machined surfaces was evaluated to identify the potential for the dental implant’s early osseointegration process, including surface roughness parameter documentation by contact and non-contact methods, surface morphology assessment by scanning electron microscopy, and surface wettability estimation using the sessile drop technique. The obtained results showed that the surface roughness parameters attributed to high osseointegration relevance (Rsk, Rku, and Rsm) were not significantly influenced by laser power, and on the other hand, the scanning speed seems to have the most prevalent effect on surface roughness when exhibiting statistical differences in all evaluated profile roughness parameters except Rvk. The obtained laser-modified surfaces were hydrophilic, with a contact angle in the range of 62.3° to 83.2°.